Peran Teacher-Student Relationship dan Emotional Exhaustion terhadap Teacher Subjective Well-being pada Guru Sekolah Dasar - Silvi Juwita; Putri Sukma Deri (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
Teacher subjective well-being is an important factor in supporting teachers’ psychological health, professional satisfaction, and teaching effectiveness in elementary education. This study aimed to examine the role of teacher-student relationship and emotional exhaustion in predicting teacher subjective well-being among elementary school teachers. A quantitative approach was employed involving 250 elementary school teachers selected through purposive sampling. Data were collected using research instruments relevant to the study variables and analyzed using multiple linear regression to determine partial and simultaneous effects. The results showed that teacher-student relationship had a positive and significant effect on teacher subjective well-being (β = 0.250; p = 0.002), indicating that positive interactions with students are associated with higher levels of teacher well-being. Conversely, emotional exhaustion had a negative and significant effect on teacher subjective well-being (β = -0.669; p < 0.001), suggesting that increased emotional fatigue reduces teachers’ well-being. Simultaneously, both variables significantly predicted teacher subjective well-being (F = 25.585; p < 0.001) and explained 17.2% of its variance (R² = 0.172). These findings emphasize the importance of strengthening supportive teacher-student relationships and reducing emotional exhaustion effectively.